Association between GPC2 polymorphisms and neuroblastoma risk in Chinese children. Issue 5 (15th March 2023) - Li, Meng; Zhang, Xinxin; Liu, Jiabin; Zhou, Chunlei; Miao, Lei; He, Jing; Wu, Haiyan; Zhang, Ruizhong
Abstract: Background: The cell surface glycoprotein glypican 2 (GPC2) has been shown to increase susceptibility to neuroblastoma, which is the most common malignancy in children. However, associations between single nucleotide polymorphism(s) of GPC2 and neuroblastoma risk remain unclarified. Methods: We conducted a case–control study to investigate two GPC2 polymorphisms (rs1918353 G>A and rs7799441 C>T) in 473 healthy controls and 402 pediatric patients with neuroblastoma. Single nucleotide polymorphism (SNP) genotyping was conducted on the samples by the TaqMan technique, and the data were subsequently analyzed by the t test, chi‐squared test, and logistic regression model. In addition, we further performed stratification analysis by age, sex, tumor site of origin, or clinical stage to control confounding factors. Results: According to the data of dominant models (GA/AA vs. GG: adjusted OR = 0.99, 95% CI = 0.76–1.29, p  = 0.943; CT/TT vs. CC: adjusted OR = 0.91, 95% CI = 0.70–1.19, p  = 0.498) or other comparisons, as well as the conjoint analysis (adjusted OR = 1.22, 95% CI = 0.93–1.59, p  = 0.152), we unfortunately proved that the analysis of single or multiple loci did not support any significant association of GPC2 polymorphisms with susceptibility to neuroblastoma. Conclusion: GPC2 polymorphisms (rs1918353 G>A and rs7799441 C>T) are unable to statistically affect neuroblastoma risk in Chinese children. Therefore, more samples, especially from patients of various ethnic backgrounds, are required to increase the sample size and verify the effect of GPC2 polymorphisms on neuroblastoma risk in the presence of ethnic factor. Abstract : We genotyped two GPC2 polymorphisms (rs1918353 G>A and rs7799441 C>T) in 402 neuroblastoma children and 473 controls. However, neither single locus nor the combination analysis supported an association between GPC2 polymorphisms and neuroblastoma risk.